Development of a novel patient-reported outcome measure to assess signs and symptoms of COVID-19 - Carla Romano; Sheri Fehnel; Jeffrey Stoddard; Jerald Sadoff; Sandy Lewis; Pauline McNulty; Eric K. H. Chan; Emily Evans; Carol Jamieson; Ashley F. Slagle; Allen Mangel; Kelly McQuarrie (SpringerOpen, 2022)
Abstract Background Given the urgent need for vaccines and treatments for coronavirus disease 2019 (COVID-19), the Symptoms of Infection with Coronavirus-19 (SIC), a comprehensive, patient-reported outcome (PRO) measure of signs and symptoms associated with COVID-19, was developed in full alignment with current US regulatory guidance to support evaluations of vaccines and treatments in development. Methods An initial version of the SIC was developed to address concepts identified through a targeted literature review and consultation with experts in infectious diseases and clinicians routinely managing COVID-19 in a hospital setting. A qualitative study was conducted in sites in the United States among 31 participants aged ≥ 18 years who were English-speaking and willing and able to provide informed consent and a self-reported history by telephone or online method. The measure was refined based on additional feedback from the clinicians and three iterative rounds of combined concept elicitation and cognitive debriefing interviews conducted with patients, caregivers, and healthy volunteers. Results Among 39 scientific articles identified in the literature review, 35 COVID-19 signs and symptoms were reported and confirmed during interviews with clinicians, patients, and caregivers. Patients and healthy participants suggested changes for refining the draft SIC to ensure consistent interpretation and endorsed both the 24-h recall period and use of an 11-point numeric rating scale (NRS) for capturing change in symptom severity. The final version of the SIC captures the daily presence or absence of 30 symptoms and a rating of severity for 25 of the 30 symptoms using an NRS for those symptoms reported as present. Conclusions The SIC comprehensively addresses observations described in the literature, by clinicians, and by patients, and captures patients' experiences with COVID-19 in a manner that minimizes complexity and facilitates completion for both patients and healthy volunteers. This measure is thus appropriate for use in clinical trials of both therapeutics and vaccines for COVID-19.